10Be cosmic-ray exposure dating of moraines and rock avalanches in the Upper Romanche valley (French Alps): Evidence of two glacial advances during the Late Glacial/Holocene transition. (15th September 2016) - Chenet, Marie; Brunstein, Daniel; Jomelli, Vincent; Roussel, Erwan; Rinterknecht, Vincent; Mokadem, Fatima; Biette, Melody; Robert, Vincent; Léanni, Laëtitia; ,
Abstract: Cosmic-ray exposure (CRE) dating of moraines allow glacier fluctuations and past climate change reconstructions. In the French Alps, there is a lack of moraine dating for the Late Glacial/Holocene transition period. Here we present a chronology of glacier advances in the Upper Romanche valley (French Alps – Massif des Ecrins) based on 10 Be CRE dating. CRE ages of moraines of 13.0 ± 1.1 ka and 12.4 ± 1.5 ka provide evidence for two stages of glacial advance or standstill at the end of the Late Glacial. The CRE dating of a rock avalanche deposit at 12.2 ± 1.5 ka is attributed to post-glacial debuttressing and reveals rapid deglaciation at the end of the Late Glacial. A CRE age of 7.1 ± 0.7 ka of a second mass-wasting, whose triggering factor is unidentified so far, indicates that up to an altitude of 2300 m a.s.l., the valley was ice-free as of ∼7 kyr at the latest. The re-evaluation of 21 moraine 10 Be CRE ages from nine glacial valleys across the Alps shows multiple glacial advances occurring at the Late Glacial/Holocene transition. These results lead to a re-evaluation of the importance of cooling events during the Allerød and the Younger Dryas in the Alps. Highlights: A new chronology of glacier in the French Alps based on moraine 10 Be CRE dating. Two glacial advance or standstill identified in the Romanche valley at the Late Glacial/Holocene transition. The 10 Be CRE dating of two rock avalanche deposits in the Romanche valley at 12.2 ± 1.5 and 7.1 ± 0.7 ka. The re-evaluation of 21 moraine 10 Be CRE ages from 9 alpine valleys.